2018
DOI: 10.1589/jpts.30.540
|View full text |Cite
|
Sign up to set email alerts
|

Does the relative muscle activation of the vastus medialis, rectus femoris, and vastus lateralis, during the various activities, change in relation to the quadriceps angle?

Abstract: [Purpose] The purpose of this study was to examine the correlation between the quadriceps angle and muscle-activation ratios for the vastus medialis, rectus femoris, and vastus lateralis during various activities. [Subjects and Methods] Seventeen heathy females were recruited. The quadriceps angles were measured with long-arm goniometers. The muscle activity of the vastus medialis, rectus femoris, and vastus lateralis were measured using electromyography under four different activity settings: walking, squatti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This could suggest that the squats interruptions resulted in the stimulation of translation initiation and myofibrillar protein synthesis. In contrast, walking had no effect on any anabolic signaling protein targets, which may be related to a lower activation of the vastus lateralis during walking compared to squatting (268). It is not clear whether type, intensity, and frequency of interruptions to sitting differentially affect markers of protein metabolism.…”
Section: Evidence From Acute Studiesmentioning
confidence: 89%
“…This could suggest that the squats interruptions resulted in the stimulation of translation initiation and myofibrillar protein synthesis. In contrast, walking had no effect on any anabolic signaling protein targets, which may be related to a lower activation of the vastus lateralis during walking compared to squatting (268). It is not clear whether type, intensity, and frequency of interruptions to sitting differentially affect markers of protein metabolism.…”
Section: Evidence From Acute Studiesmentioning
confidence: 89%
“…When exercising on a NMT or MT, different gait patterns occur even at the same given speed, creating different tasks in movement (S. M. C. Lee et al, 2008), while changes of speed and gait have been shown to effect muscle activation (Cappellini, Ivanenko, Poppele, & Lacquaniti, 2006). Recent studies have found correlations between a greater hip-knee-ankle (HKA) angle and an increase in medial muscle activation (Kim, Bae, Lee, & Lee, 2016;N. Lee, 2018), however in our study there was a significant difference only in the VL during the walking condition.…”
Section: Discussionmentioning
confidence: 99%